Development of a semi‐automated method for tumour budding assessment in colorectal cancer and comparison with manual methods. Issue 3 (10th November 2021) - Fisher, Natalie C; Loughrey, Maurice B; Coleman, Helen G; Gelbard, Melvin D; Bankhead, Peter; Dunne, Philip D
Abstract : Aims: Tumour budding (TB) is an established prognostic feature in multiple cancers but is not routinely assessed in pathology practice. Efforts to standardise and automate assessment have shifted from haematoxylin and eosin (H&E)‐stained images towards cytokeratin immunohistochemistry. The aim of this study was to compare manual H&E and cytokeratin assessment methods with a semi‐automated approach built within QuPath open‐source software. Methods and results: TB was assessed in cores from the advancing tumour edge in a cohort of stage II/III colon cancers ( n  = 186). The total numbers of buds detected with each method were as follows: manual H&E, n  = 503; manual cytokeratin, n  = 2290; and semi‐automated, n  = 5138. More than four times the number of buds were identified manually with cytokeratin assessment than with H&E assessment. One thousand seven hundred and thirty‐four individual buds were identified with both manual and semi‐automated assessments applied to cytokeratin images, representing 75.7% of the buds identified manually ( n  = 2290) and 33.7% of the buds detected with the semi‐automated method ( n  = 5138). Higher semi‐automated TB scores were due to any discrete area of cytokeratin immunopositivity within an accepted area range being identified as a bud, regardless of shape or crispness of definition, and to the inclusion of tumour cell clusters within glandular lumina ('luminal pseudobuds'). Although absolute numbers differed, semi‐automated and manual bud counts were strongly correlated across cores ( ρ  = 0.81, P  < 0.0001). All methods of TB assessment demonstrated poorer survival associated with higher TB scores. Conclusions: We present a new QuPath‐based approach to TB assessment, which compares favourably with established methods and offers a freely available, rapid and transparent tool that is also applicable to whole slide images. Abstract :